Neurotrophic growth factors for the treatment of amyotrophic lateral sclerosis: where do we stand ? - Henriques, Alexandre; Pitzer, Claudia; Schneider, Armin (Frontiers in Neuroscience, 2010)
Amyotrophic lateral sclerosis (ALS) is a devastating neurodegenerative disease that results in progressive loss of motoneurons, motor weakness and death within 3-5 years after disease onset. Therapeutic options remain limited despite substantial number of approaches that have been tested clinically. Many neurotrophic growth factors are known to promote the survival of neurons and foster regeneration in the CNS. Various neurotrophic factors have been investigated preclinically and clinically for the treatment of ALS. Although preclinical data appeared promising, no neurotrophic factors succeeded yet in a clinical phase III trial. In this review we discuss the rationale behind those factors, possible reasons for clinical failures, and argue for a renewal of hope in this powerful class of drugs for the treatment of ALS.